The Evaluation of Metal Co-ordinating Bis-Thiosemicarbazones as Potential Anti-malarial Agents - Akladios, Fady N.; Andrew, Scott D.; Boog, Samantha J.; de Kock, Carmen; Haynes, Richard K.; Parkinson, Christopher J. (Medicinal Chemistry, 2019)
Background: The emergence of resistance to the artemisinins which are the current mainstays for antimalarial chemotheraphy has created an environment where the development of new drugs acting in a mechanistally discrete manner is a priority. Objective: The goal of this work was to synthesize ane evaluate bis-thiosemicarbazones as potential antimalarial agents. Methods: Fifteen compounds were generated using two condensation protocols and evaluated in vitro against the NF54 (CQ sensitive) strain of Plasmodium falciparum. A preliminary assessment of the potential for human toxicity was conducted in vitro against the MRC5 human lung fibroblast line. Results: The activity of the bis-thiosemicarbazones was highly dependent on the nature of the arene at the core of the structure. The inclusion of a non-coordinating benzene core resulted in inactive compounds, while the inclusion of a pyridyl core resulted in compounds of moderate or potent antimalarial activity (4 compounds showing IC50 < 250 nM). Conclusion: Bis-thiosemicarbazones containing a central pyridyl core display potent antimalarial activity in vitro. Sequestration and activation of ferric iron appears to play a significant role in this activity. Ongoing studies are aimed at further development of this series as potential antimalarials.
Keywords: thiosemicarbazone